Community use of antibiotics and development of bacterial resistance: a case-control study in Italy. (13th November 2019) - Ferrante, G; Massari, M; Da Cas, R; Pantosti, A; Pezzotti, P; Moser, V; Pagani, E; Aschbacher, R; Traversa, G
Abstract: Background: Antibiotic resistance is now a global emergency. An increasing number of infections are becoming difficult to treat and lead to longer hospitalizations, higher medical costs and increased mortality. The aim of this study is to assess, in a population at low prevalence of use of antibiotics, whether a previous use of these drugs is associated with the occurrence of clinically relevant resistance of E.coli to fluoroquinolones (FQs), one of the most widespread and critical bacteria resistance in Italy. Methods: Through a data linkage of databases of the health information systems of the Province of Bolzano (Italy) a case-control study was carried out using 2016 data. All subjects for which the resistance of E. coli to FQs was tested by the regional microbiology reference laboratory were included in the study. Those with a positive FQs-resistant E.coli isolate were defined as cases (n = 409), while the others were considered controls (n = 933). For each subject the total number of prescriptions of any antibiotics and the total number of prescriptions of FQs in the previous year were detected through a record linkage with the drug prescription database. Information on potential confounding factors (age, gender, number of hospital admissions, days of hospitalization, number of surgeries, diagnosis of chronic diseases) were obtained from the database of hospital admissions. Multivariate logistic regression analysis was used to study the association between previous use of antibiotics (any and FQs only) and development of E.coli resistance to FQs. Results: It was observed that for each unit increase in the number of prescriptions of any antibiotic, the probability for E.coli to develop FQs resistance significantly rises by 16%. This probability is much higher (45%) if the prescribed antibiotic is a FQ. Conclusions: This study confirms the association between previous consumption of antibiotics and the onset of resistance even in an area with a low prevalence of use. Key messages: The results of this study reiterate the need to prescribe and dispense antibiotics only when they are really needed. Health information systems allows to study the role of antibiotic use in the development of bacterial resistance, providing useful information for audit interventions among healthcare professionals.